2014
DOI: 10.1186/1742-4690-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus Tat associates with a specific set of cellular RNAs

Abstract: BackgroundHuman Immunodeficiency Virus 1 (HIV-1) exhibits a wide range of interactions with the host cell but whether viral proteins interact with cellular RNA is not clear. A candidate interacting factor is the trans-activator of transcription (Tat) protein. Tat is required for expression of virus genes but activates transcription through an unusual mechanism; binding to an RNA stem-loop, the transactivation response element (TAR), with the host elongation factor P-TEFb. HIV-1 Tat has also been shown to alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…6E. The amount of RNA extracted from samples immunoprecipitated with antiTat or IgG was about 25 and 1 ng/l, respectively, confirming that Tat can associate with cellular RNAs, as recently reported (55). Semiquantitative RT-PCR revealed the presence of both E10 included (top band) and E10 excluded (lower band) in the samples in which Tat and TAU were present (Fig.…”
Section: Tau 3r Isoforms Are Increased and Sc35 Is Dysregulated In Husupporting
confidence: 87%
See 1 more Smart Citation
“…6E. The amount of RNA extracted from samples immunoprecipitated with antiTat or IgG was about 25 and 1 ng/l, respectively, confirming that Tat can associate with cellular RNAs, as recently reported (55). Semiquantitative RT-PCR revealed the presence of both E10 included (top band) and E10 excluded (lower band) in the samples in which Tat and TAU were present (Fig.…”
Section: Tau 3r Isoforms Are Increased and Sc35 Is Dysregulated In Husupporting
confidence: 87%
“…In addition, recent reports indicating that cellular factors such as SC35 can function in a manner similar to Tat (53,54) further support the possibility that Tat itself may compete with cellular proteins or with host RNA species to affect RNA metabolism. This possibility was confirmed by RNA immunoprecipitation coupled with microarray analysis, which demonstrated that Tat can interact with cellular RNAs in T cells (55). Although in that report TAU RNA was not detected, likely due to the low abundance of TAU in T cells, there is a surprising similarity between Tau exon 10 and TAR LTR stem-loop structures, suggesting the possibility of a Tat-TAU RNA interaction.…”
Section: Discussionmentioning
confidence: 83%
“…In another experiment, K50 interacted with G34 of TAR RNA loop, indicating that the protein‐RNA cross‐link occurred at K50 position whereas mutation at G34 to U34 significantly reduced Tat‐Cyclin T1 binding capacity . Mutations of the first two lysines at 50 and 51 positions to serine and glycine (K50S and K51G), respectively, showed a decrease in Tat activity by 50% in vivo . Interesting results assessing transactivation of HIV LTR came from molecular dynamics simulations combined with in vitro experiments by the Carloni group.…”
Section: Basic Domain Functions As An Rna Binding Motifmentioning
confidence: 99%
“…In addition to viral RNA, Tat is believed to interact with cellular RNAs. The ability of Tat basic domain to associate with human RNAs was examined via immunoprecipitation analysis of the wild‐type Tat and its mutated form, K50S‐K51G . The mutant form showed a significant decrease in interaction with RNA, in particular Tat‐bound FADD and TNFRSF8 RNAs, leading to speculations that, in addition to TAR RNA, Tat was able to associate with the specific set of human RNAs for which an intact basic domain was required .…”
Section: Basic Domain Functions As An Rna Binding Motifmentioning
confidence: 99%
See 1 more Smart Citation